Validation of MIPAS IMK/IAA methane profiles - Laeng, Alexandra; Plieninger, J.; von Clarmann, T.; Grabowski, U.; Stiller, G.; Eckert, E.; Glatthor, N.; Haenel, F.; Kellmann, S.; Kiefer, M.; Linden, A.; Lossow, S.; et al. (Atmospheric measurement techniques, 2015)
The Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) is an infrared (IR) limb emission spectrometer on the Envisat platform. It measures trace gas distributions during day and night, pole-to-pole, over an altitude range from 6 to 70 km in nominal mode and up to 170 km in special modes, depending on the measurement mode, producing more than 1000 profiles day−1. We present the results of a validation study of methane, version V5R_CH4_222, retrieved with the IMK/IAA (Institut für Meteorologie und Klimaforschung, Karlsruhe/Instituto de Astrofisica de Andalucia, Grenada) MIPAS scientific level 2 processor.
Gesehen am 05.06.2020